Encoding the Ethiopic Miracles of Mary - Dorothea Reule (Journal of the Text Encoding Initiative)
This article will illustrate the challenges of digitizing of historical manuscript catalogues, taking as an example the widespread and complex work of the “Miracles of Mary.” This work is typically composed of framing texts and miracle texts proper, often accompanied by miniatures, and it circulates in collections of varying standardization. A flexible encoding system with different identifiers for textual units and art themes has been developed, answering the most common challenges of encoding the Ethiopic literary tradition, improving the cataloguing.